Comparative Analysis of Apology Strategies of English and Korean Series - putri, Sita Arum Priono; Sugiharti, Dona Rahayu (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2024)
This study aims to identify the types of apology strategies used by characters in English and Korean series using Olshtain and Cohen's (1986) theory. Additionally, this study aims to discover the differences in apology strategies between the English series "Secret Invasion" and the Korean series "Moving." The author employs a descriptive qualitative method in this research. The findings reveal that the English series employs 5 types of apology strategies, namely 2 expressions of apology, 1 offer of repair, 7 explanations of account, 1 acknowledgment of responsibility for the offense, and 2 promises of forbearance. The English series predominantly uses explanations of account because English culture tends to ignore social differences and apology strategies, and does not consider age or social status. In contrast, the Korean series uses only 4 types of apology strategies, namely 33 expressions of apology, 7 explanations of account, 1 acknowledgment of responsibility for the offense, and 1 promise of forbearance. The Korean series frequently uses apology phrases because Koreans pay more attention to age when apologizing and tend to apologize directly, as this is considered more polite and demonstrates feelings of guilt for mistakes made.